Increasing the longitudinal bending stiffness of runners` habitual shoes: An appropriate choice for improving running performance? - Flores, N.; Rao, G.; Berton, E.; Delattre, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
This study analysed the effects of increasing the longitudinal bending stiffness (LBS) of runners` habitual shoes on the metabolic energetic demand, lower limb muscle activation and stride spatiotemporal parameters during a prolonged running session through classical group investigation, as well as a more individualised approach. Eleven recreational male participants ran overground for 40 min at 95% of their ventilatory anaerobic threshold with their own shoes or their shoes with higher LBS (stiff carbon plate inserted under insole). The net energetic cost of running, lower leg muscle activation and spatiotemporal parameters were measured during the prolonged running. The variables of interest were analysed for 1 min in seven time intervals. There were no main effects of LBS or interaction effects with running duration on the group averaged variables. Overall, the participant-specific metabolic effects induced by an increased shoe LBS were not beneficial. Beneficial metabolic effects were more likely to occur when the increased LBS induced a decrease or no change in the ground contact time relative to their habitual shoes, as well as for taller runners. Increasing the LBS in runners` habitual shoes did not induce systematic metabolic effects for all the runners and may not be beneficial for performance purposes if the runners` shoe habits were too disrupted.